King James II in Foreign Historiography: the Main Scientifi c Trends and Approaches . - Stankov Kirill (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
The fate of the tragic ﬁgure of the British king James II Stuart is considered in the article. In this paper the author pays speсial attention to the history of investigation of the character and politics of this person by the British historians, as well as by the leading European and American specialists on the Early Modern Time. The estimates of James II are of vast variety in the British historiography but at the same time diﬀ erent authors have some similar features in their attitude. Except the apologists the British historians on the whole criticized this king and explain that the majority of the problems connected with him are based on the religious factor that is not really right. On the other hand there are some diﬀerences in this negative approaches among various scientiﬁ c schools of British historiography. The Whigs stated that James II tried to limit the personal rights of the Englishmen which was the main result of the English revolution of the middle of the 17th century. The Tories proved that the king neglected the gentry’s property rights and tried to transform the dualistic monarchy into absolutism. The Positivists thought that James II supported the Catholic Counterreformation and fought against the Enlightenment. The revisionists and postrevisionists tried to revalue the person of James II based on the true scientiﬁc foundations. A special view on James II’ policy is produced by Non-British authors: German, French and American historians.